IJPE 2018
DOI: 10.23940/ijpe.18.01.p14.134143
|View full text |Cite
|
Sign up to set email alerts
|

Using SIR Model to Simulate Emotion Contagion in Dynamic Crowd Aggregation Process

Abstract: Emotion contagion is an indispensable behavior in a dynamic crowd, especially in an evacuation situation. As a consequence, generating emotion contagion results is very useful in the crowd simulation field. However, because the topology of the crowd usually keeps changing dynamically, computing the contagion process is a challenge. In this paper, we represented our research about the emotion contagion effects on the virtual pedestrian dynamic aggregation process. First of all, we calculated individuals' moving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…While bottom up attempts to predict collective emotions have been relatedly sparce, there are many computational that attempt to capture collective emotions (Bosse et al, 2014;Fan et al, 2018;Gao & Liu, 2017;Garcia et al, 2011;Haeringen et al, 2021;Hill et al, 2010;Riahi, 2015;Wang et al, 2015;Xiang et al, 2018;Xu et al, 2021). These models are built with the hope that they could provide preliminary signals for increase in collective emotion or maybe even be fitted to actual data in ways that that would help predict the unfolding of collective emotion.…”
Section: Predicting Collective Emotionsmentioning
confidence: 99%
“…While bottom up attempts to predict collective emotions have been relatedly sparce, there are many computational that attempt to capture collective emotions (Bosse et al, 2014;Fan et al, 2018;Gao & Liu, 2017;Garcia et al, 2011;Haeringen et al, 2021;Hill et al, 2010;Riahi, 2015;Wang et al, 2015;Xiang et al, 2018;Xu et al, 2021). These models are built with the hope that they could provide preliminary signals for increase in collective emotion or maybe even be fitted to actual data in ways that that would help predict the unfolding of collective emotion.…”
Section: Predicting Collective Emotionsmentioning
confidence: 99%
“…In the 1920s, Kermack and McKendrick (1927) first modeled the infection dynamics of a disease, whereas the population is divided into three compartments: the susceptible, the infected and the recovered (SIR). The SIR model describes the state dynamics of nodes in a general system, and it sees adoption in a variety of application contexts, such as data transmissions in mobile Inter-vehicular communication networks (Mashwama et al 2020), and dynamic emotion contagion in a crowd of evacuees (Xiang et al 2018). After that, the development of various epidemiological models and mechanisms subsequently emerged, often assuming a well-mixed population that can be described by an SIR-type system dynamics (Daley and Kendall 1964;Maki and Thompson 1973;Sudbury 1985;Rey et al 2016).…”
Section: Rumor Transmission Modelmentioning
confidence: 99%
“…As far as we know, the original model and improved version of SIR are applicable to not only WSN networks, but also other complex networks, and the scope of application is quite extensive. For example, Xiang et al [23] used SIR model to simulate emotion contagion in dynamic crowd aggregation process, and they found that the SIR model can effectively improve the fidelity of emotional interaction processes and crowd aggregation. Lamb et al [24] described the SIR stochastic epidemic model of computer virus by combining the time-Markov chain of the minimum traffic model and the control of virus propagation.…”
Section: Related Workmentioning
confidence: 99%